Effect of hydrofluoric acid-based etchant at an elevated temperature on the bond strength and surface topography of Y-TZP ceramics - Mi-Kyung Yu; Myung-Jin Lim; Noo-Ri Na; Kwang-Won Lee (Restorative Dentistry & Endodontics, 2020)
ObjectivesThis study investigated the effects of a hydrofluoric acid (HA; solution of hydrogen fluoride [HF] in water)-based smart etching (SE) solution at an elevated temperature on yttria-stabilized tetragonal zirconia polycrystal (Y-TZP) ceramics in terms of bond strength and morphological changes.Materials and MethodsEighty sintered Y-TZP specimens were prepared for shear bond strength (SBS) testing. The bonding surface of the Y-TZP specimens was treated with 37% phosphoric acid etching at 20°C–25°C, 4% HA etching at 20°C–25°C, or HA-based SE at 70°C–80°C. In all groups, zirconia primers were applied to the bonding surface of Y-TZP. For each group, 2 types of resin cement (with or without methacryloyloxydecyl dihydrogen phosphate [MDP]) were used. SBS testing was performed. Topographic changes of the etched Y-TZP surface were analyzed using scanning electron microscopy and atomic force microscopy. The results were analyzed and compared using 2-way analysis of variance.ResultsRegardless of the type of resin cement, the highest bond strength was measured in the SE group, with significant differences compared to the other groups (p < 0.05). In all groups, MDP-containing resin cement yielded significantly higher bond strength values than MDP-free resin cement (p < 0.05). It was also shown that the Y-TZP surface was etched by the SE solution, causing a large change in the surface topography.ConclusionsBond strength significantly improved when a heated HA-based SE solution was applied to the Y-TZP surface, and the etched Y-TZP surface was more irregular and had higher surface roughness.